Recruitment and Retention for Community‐Based eHealth Interventions with Populations of Low Socioeconomic Position: Strategies and Challenges. (7th January 2013) - Nagler, Rebekah H.; Ramanadhan, Shoba; Minsky, Sara; Viswanath, K.
<x xml:space="preserve">Abstract</x> Given persistent communication inequalities, it is important to develop interventions to improve Internet and health literacy among underserved populations. These goals drove the Click to Connect project, a community‐based eHealth intervention that provided novice computer users of low socioeconomic position with broadband Internet access, training classes, a Web portal, and technical support. In this article, we describe the strategies used to recruit and retain this population, the budgetary implications of such strategies, and the challenges and successes we encountered. Results suggest that personal contact between study staff and participants and provision of in‐depth technical support were central to successful recruitment and retention. Such investments are essential to realize the promise of eHealth with underserved populations.